Laboratory-Acquired Dengue Virus Infection, United States, 2018 - Sharp, Tyler M. (Emerg Infect Dis, 2020)
Investigation of a dengue case in a laboratory worker in North Carolina, USA, revealed that the case-patient prepared high-titer dengue virus stocks soon before illness onset. Improper doffing of gloves with an open finger wound likely resulted in cutaneous exposure. This case reinforces recommendations for enhanced precautions when working with high-titer dengue virus.